A new telesurgery generation supported by 5G technology: benefits and future trends - Mendoza Navarro, Emmanuel (Procedia Computer Science, 2022)
Telesurgery is a medical practice that has been developed for the last two decades. The idea is very simple, a highly trained surgeon performs a surgical intervention on a patient while being away from the operating room. The surgery execution is done through two principal equipment: a robotic one installed in the operating room and a remote station from which the surgeon controls the robot. The communication between both parties is established through a specialized internet connection. The research and development of these remote surgery systems have been revolutionizing the medicine praxis due to its multiple benefits. During the last years, these systems have substantially improved many of their main limiting aspects, furthermore, the incorporation of 5G technology is a booster in telesurgery possibilities. Nonetheless, telesurgery benefits are not available for everyone because telesurgery requires high-cost equipment incorporation, specialized facilities and staff. This is the main reason for which health systems in developing countries dismiss its application.
This paper explains telesurgery with a brief historical review and future trends of this technology and also presents anvalue proposition that may facilitate telesurgery practice in remote medical units. Focusing on the implementations and benefits that 5G technology can provide to the development of telesurgery as a development opportunity medical praxis linked to the accelerated growth of high-speed networks in the connected world.
Keywords: 5G; Medicine; Robotic; System; Telesurgery